CT Venography in Diagnosing Deep Vein Thrombosis Having Suspicion of patients with Pulmonary Embolism - Rafique, M. Salman; Jabeen, Mahwish; Kundi, Sana; Alam, Shahjehan; Safi, Abdullah; Abid, Hadia; S. Umer, Ummara; Rabbani, Saima (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: CT venography in diagnosing DVT in cases with suspicion of pulmonary embolism taking doppler USG as gold standard Methodology: A cross sectional study was conducted in Radiology Department of a tertiary care Hospital. Forty cases with suspicion of pulmonary embolism were selected. CT venography from iliac to calf veins was done with CT pulmonary angiogram. Doppler USG was taken as gold standard. Results: The overall sensitivity, specificity, positive & negative predictive values for CT venography were100%, 94.1%, 75%, and 100% respectively. Conclusions: Sensitivity, specificity and negative predictive value of CT venography was significant in diagnosing DVT with strong suspicion of patients with pulmonary embolism.